Elementary school students’ learning difficulties on distance learning during COVID-19: the psychological approach - Aquami Aquami; Mifathul Husni; Dian Andesta Bujuri; Nyayu Khodijah; Kusumasari Kartika Hima Darmayanti; Amilda Amilda; Masnun Baiti; Erlina Anggraini; Marjon C. Malacapay (International Journal of Evaluation and Research in Education (IJERE), 2024)
During the COVID-19 period, pupils in primary schools have encountered various learning challenges. In Indonesia, this occurs in every primary school. This study intends to lighten the psychological aspect of distance learning challenges. This study employs a mixed-method methodology by integrating qualitative research, a case study technique, and quantitative description (n=414). Researchers looked at three primary school models in South Sumatra and Special Region of Yogyakarta: Model A, which used technology-based online learning; Model B, which integrated online and offline learning; and Model C, which only used WhatsApp group-based offline learning. Focus group discussions, observations, documentation, and interviews with teachers, parents, and students were all undertaken by the researchers. They also distributed open-ended and closed-ended questionnaires via Google Form. The interactive Miles, Huberman, and Saldana’s models were used to analyze data. The findings demonstrated that children in all three school models encountered similar learning challenges. Still, in Model C, the complexity of those challenges was more significant than in Model A and Model B. Learning challenges included issues with comprehending topics, struggling to solve the problems with completing tasks, and working with self-study. The lack of essential psychological needs, such as the ability to interact and actualize oneself, as well as the boredom or monotony of students when pursuing distance learning, are some of the causes of learning challenges. The findings of this study have consequences for teachers and psychologists, who should pay attention to children’s fundamental needs to improve learning motivation and academic progress in primary school pupils.